Loofah sponge-based cross-linked hydrophobic oleophylic modified oil absorption material and preparation method thereof

By cross-linking and grafting and covalent hydrophobic lipophilic modification treatment on the loofah, the problem of insufficient adsorption efficiency and durability of the loofah is solved, and efficient oil-water separation and improved reuse rate are achieved.

CN119425633AActive Publication Date: 2025-02-14CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510045705.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-14
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

In the prior art, the natural hydrophilic and lipophilic properties of the loofah limit its adsorption efficiency and oil-water separation effect, and the physical coating method of the hydrophobic modified material is unstable, resulting in the hydrophobic layer falling off during reuse, affecting the loofah. Durability and reusability.

Method used

By conducting a cross-linking grafting reaction within the pretreated loofah in the lye, bisphenol dicyclic glycerol ether is introduced, and hydrophobic lipophilic long-chain alkyl compound is covalently grafted on its surface to form a loofah-based cross-linking hydrophobic hydrophobic hydrophobic hydrophobic hydrophobic hydrophobic Lipophilic modified oil-absorbing material.

Benefits of technology

It significantly improves the oil-water separation performance and durability of the loofah, enhances its stability and reuse rate under complex environmental conditions, and simplifies the modification process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425633A_ABST
    Figure CN119425633A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a loofah sponge-based cross-linked hydrophobic oleophylic modified oil absorption material. The preparation method comprises the following steps: cross-linking grafted bisphenol bicyclic glyceryl ether among fibers in loofah sponge pretreated by alkali liquor to obtain cross-linked modified loofah sponge; a hydrophobic and oleophylic long-chain alkyl compound is added into a reaction solution obtained after the cross-linking grafting reaction, stirring reaction continues, the loofah sponge-based cross-linked hydrophobic and oleophylic modified oil absorption material is obtained, and the mass ratio of the loofah sponge pretreated with the alkali liquor to the long-chain alkyl compound is 1: (0.4-0.8). The invention also discloses the loofah sponge-based cross-linked hydrophobic oleophylic modified oil absorption material prepared by the preparation method. The oil absorption material prepared by the invention has excellent hydrophobic and oleophylic properties and reusability, and the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid adsorbents, and in particular to a loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material and a preparation method thereof. Background Art

[0002] Luffa sponge has a unique spatial structure composed of macropores and micropores. In addition, it is low-cost, renewable and easily biodegradable. It can be used as a biomass porous oil-absorbing material.

[0003] However, the natural hydrophilic and lipophilic properties of loofah limit its adsorption efficiency and oil-water separation effect, making it difficult to meet the demand for efficient oil-water separation in practical applications. Although a variety of low surface energy materials have been used to hydrophobically modify loofah, most of these hydrophobic materials are only attached to the surface of loofah by physical coating, lacking a stable chemical bond connection, resulting in the hydrophobic layer easily falling off during repeated use, thus affecting the reuse rate of loofah. In addition, loofah also needs to face the challenges of complex environmental conditions such as pH changes and temperature fluctuations in practical applications. The original loofah is prone to degradation or failure under these conditions, thereby reducing its oil absorption performance and service life. Therefore, it is particularly important to chemically modify loofah to improve its oil-water separation performance and enhance durability. However, although the existing chemical modification technology has improved the performance of loofah to a certain extent, the improvement effect is limited and the modification process is relatively complicated. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material and a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material prepared by the preparation method, with the aim of performing simple and efficient chemical modification on the luffa and significantly improving the oil-water separation performance and durability of the luffa.

[0005] The technical solution of the present invention is as follows: A method for preparing a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material comprises the following steps: (1) Bisphenol dicyclic glycerol ether is cross-linked and grafted between the fibers of the loofah pretreated with alkali solution to obtain a cross-linked modified loofah; (2) Adding a hydrophobic and lipophilic long-chain alkyl compound to the reaction solution after the cross-linking grafting reaction in step (1), continuing the stirring reaction, and obtaining a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material, wherein the mass ratio of the luffa pretreated with alkali solution to the long-chain alkyl compound is 1:(0.4-0.8).

[0006] Furthermore, the step (1) specifically comprises adding the loofah sponge pretreated with alkali solution into ethanol, adding bisphenol diglycerol ether, and adding an organic acid as a catalyst to carry out a cross-linking grafting reaction, wherein the mass ratio of the loofah sponge pretreated with alkali solution, bisphenol diglycerol ether, and the organic acid is 1: (0.1-0.3): (0.03-0.07).

[0007] Furthermore, the organic acid is one of formic acid and acetic acid.

[0008] Furthermore, the cross-linking grafting reaction in step (1) is carried out by stirring at 40-60° C. for 6-10 hours.

[0009] Furthermore, the hydrophobic and lipophilic long-chain alkyl compound is a hydrophobic and lipophilic alkylene oxide.

[0010] Furthermore, after adding the hydrophobic and lipophilic long-chain alkyl compound in step (2), the reaction is continued with stirring at 40-60° C. for 6-10 hours. After the reaction, the mixture is filtered, repeatedly washed with ethanol, and dried to obtain the luffa-based cross-linked hydrophobic and lipophilic modified material.

[0011] Furthermore, the alkaline solution pretreatment is to soak the loofah in a 2% to 15% NaOH aqueous solution, stir and treat it at 60 to 100° C. for 2 to 5 hours, and then wash it with deionized water until it is neutral.

[0012] Another technical solution of the present invention is a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material, which is prepared by the above-mentioned preparation method of the luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material.

[0013] The present invention utilizes the ring-opening reaction of hydroxyl and epoxy groups, and first realizes the cross-linking grafting of bisphenol dicyclic glycerol ether inside the loofah. The cross-linking modification not only further improves the porosity and specific surface area of ​​the loofah, but also introduces a series of lipophilic groups such as benzene ring structure, methylene group, ether group, etc. More importantly, the cross-linking modification significantly enhances the structural stability of the loofah, ensuring that in practical applications, the structure of the loofah can resist external extrusion without being destroyed. Subsequently, the present invention utilizes the new hydroxyl generated by the ring-opening reaction as a binding site to covalently graft a large amount of hydrophobic and lipophilic long-chain alkyl compounds in the cross-linked grafted modified loofah. This step not only further enriches the hydrophobic and lipophilic groups of the loofah, but also ensures that the hydrophobic and lipophilic substances can be tightly attached to the loofah through the firm connection of covalent bonds, effectively avoiding the problem of falling off during repeated use.

[0014] The advantages of the present invention compared with the prior art are: (1) The method for cross-linking hydrophobic and lipophilic modification of loofah provided by the present invention has simple and clear steps, efficient and convenient operation, and significantly reduces production cost and time cost.

[0015] (2) The modified loofah prepared by the present invention not only has a rich pore structure, but also has a large number of hydrophobic and lipophilic groups, and thus has a very excellent oil-water separation ability.

[0016] (3) The modified loofah prepared by the present invention not only has excellent oil-water separation performance, but also improves its durability and environmental adaptability through the dual enhancement of cross-linking modification and covalent hydrophobic and lipophilic modification. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The adsorption amount of engine oil by the loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material prepared in Example 1 of the present invention changes with the number of cycles.

[0018] Figure 2 The contact angle of the loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material prepared in Example 1 of the present invention to water changes with the number of cycles. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the embodiments, but are not intended to be limiting of the present invention.

[0020] Example 1 A method for preparing a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material comprises the following steps: After peeling and removing the seeds from the ripe loofah fruit, immerse it in distilled water and squeeze it several times until no impurities fall off and the color changes. Then immerse the loofah in new distilled water again, changing the water every 3 hours, take it out after 12 hours, dry it naturally, and cut the loofah into 0.3 cm samples. Soak the sample in 10% NaOH aqueous solution, stir it at 80℃ for 3 hours, take it out, wash it with distilled water until it is neutral, and dry it for later use.

[0021] 1 g of loofah pretreated with alkali solution was added to ethanol, followed by stirring and adding 0.1 g of bisphenol diglycerol ether and 0.03 g of formic acid. The reaction solution was stirred and reacted at 40°C for 10 hours, and then 0.4 g of octadecane oxide was added to the reaction solution. The reaction was stirred and reacted at 40°C for 10 hours. After the reaction, the loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material was obtained by filtration, repeated washing with ethanol, and drying.

[0022] The relevant performance experiments of the loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material of Example 1 are as follows: Water contact angle test: A contact angle tester (model SDC-350H) was used to characterize the hydrophobicity of the material. The sample was adhered to a glass slide and water was dripped on the sample surface with a syringe. The amount of water added was 5 μl. Five different positions of each sample were measured and the average value was taken. The results are listed in Table 1.

[0023] Oil absorption capacity test: First, the sample was placed in a 60°C oven for 2 hours for drying and then weighed. The initial weight was recorded as M 0. Then place the sample in a mixture of engine oil and water. After 15 minutes, take out the sample and place it on a metal filter. After 3 minutes of static dripping, place the sample in a 60℃ oven for drying for 4 hours and weigh it. The weight is recorded as M t Each sample was measured three times and the average value was taken. The oil absorption capacity (AR) of the sample was calculated according to the following formula. The results are listed in Table 1.

[0024]

[0025] Reusability: Mechanical extrusion is used to squeeze out the oil adsorbed by the impregnated sample. Each oil-water separation and each extrusion is regarded as one cycle. The changes in the sample water contact angle and oil absorption capacity with the number of extrusions are recorded to determine the reusability of the sample. The results of Example 1 are shown in Figure 1 and Figure 2 As shown, it can be seen that with the increase in the number of cycles, the prepared luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material only shows a slight decrease in oil absorption and water contact angle, and still maintains excellent oil absorption capacity and outstanding hydrophobic properties. It shows that the luffa cross-linked hydrophobic and lipophilic modification technology adopted by the present invention effectively enhances the durability of the luffa. Specifically, the cross-linking modification gives the luffa a stronger compressive resistance in practical applications, effectively preventing its structure from being squeezed and destroyed when subjected to force; and the covalent hydrophobic and lipophilic modification ensures that the hydrophobic layer is not easy to fall off during repeated use, thereby greatly improving the reuse rate of the luffa.

[0026] Example 2 The loofah was treated with alkali solution in the same manner as in Example 1. 1 g of the loofah pretreated with alkali solution was added to ethanol, followed by stirring and adding 0.2 g of bisphenol dicycloglycerol ether and 0.05 g of acetic acid, and the reaction solution was stirred and reacted at 50° C. for 8 h, and then 0.6 g of octadecane oxide was added to the reaction solution, and the reaction was continued to be stirred and reacted at 50° C. for 8 h. After the reaction, the loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material was obtained after suction filtration, repeated washing with ethanol, and drying. The water contact angle and oil absorption capacity of the loofah were measured according to the relevant performance experiment of the product in Example 1, and the results are listed in Table 1.

[0027] Example 3 The loofah was treated with alkali solution in the same manner as in Example 1. 1 g of loofah pretreated with alkali solution was added to ethanol, followed by stirring and adding 0.3 g of bisphenol dicycloglycerol ether and 0.07 g of formic acid, and the reaction solution was stirred and reacted at 60° C. for 6 hours, and then 0.8 g of octadecane oxide was added to the reaction solution, and the reaction was continued to be stirred and reacted at 60° C. for 6 hours. After the reaction, the loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material was obtained after suction filtration, repeated washing with ethanol, and drying. The water contact angle and oil absorption capacity of the loofah were measured according to the relevant performance experiment of the product in Example 1, and the results are listed in Table 1.

[0028] Comparative Example 1 A preparation method of a luffa-based cross-linked modified oil-absorbing material: luffa is treated with alkali solution in the pre-treatment manner in Example 1. 1 g of luffa pre-treated with alkali solution is added to ethanol, and then 0.1 g of bisphenol dicycloglycerol ether and 0.03 g of formic acid are added with stirring, and the reaction solution is stirred and reacted at 40° C. for 10 hours. After the reaction, the luffa-based cross-linked modified oil-absorbing material is obtained after suction filtration, repeated washing with ethanol, and drying. The water contact angle and oil absorption capacity of the luffa-based cross-linked modified oil-absorbing material are measured according to the relevant performance experiment of the product in Example 1, and the results are listed in Table 1.

[0029] Comparative Example 2 A preparation method of a hydrophobic and lipophilic modified oil-absorbing material based on loofah: the loofah is treated with alkali solution in the pretreatment method in Example 1. 1g of the loofah pretreated with alkali solution is added to ethanol, and then 0.4g of octadecane oxide and 0.03g of formic acid are added with stirring, and the reaction solution is stirred and reacted at 40°C for 10h. After the reaction, the hydrophobic and lipophilic modified oil-absorbing material based on loofah is obtained after suction filtration, repeated washing with ethanol, and drying. The water contact angle and oil absorption capacity of the loofah are measured according to the relevant performance experiment of the product in Example 1, and the results are listed in Table 1.

[0030] Table 1 Water contact angle and adsorption amount of engine oil of adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-2

[0031] In the embodiment of the present invention, the prepared luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material has a hydrophobic substance tightly grafted into the luffa through a stable covalent bond, which significantly enhances the hydrophobic properties of the luffa, and its surface water contact angle is as high as 149.7°, showing excellent hydrophobic properties. In addition, the adsorbent material also has a rich pore structure and a large number of lipophilic groups, which makes it show excellent ability in oil-water separation, and the adsorption amount of silicone oil can reach 18.9g / g.

[0032] In contrast, the loofah in Comparative Example 1 was only subjected to crosslinking modification without further covalent hydrophobic modification, while Comparative Example 2 was only subjected to covalent hydrophobic lipophilic modification. Therefore, the modified loofahs prepared in these two comparative examples are not comparable to the modified loofahs in the examples in terms of the number of lipophilic groups and the richness of the pore structure, which directly leads to a significant decrease in their hydrophobicity and silicone oil adsorption.

Claims

1. A method for preparing a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material, characterized in that: The following steps are involved: (1) Bisphenol dicyclic glycerol ether is cross-linked and grafted between the fibers of the loofah pretreated with alkali solution to obtain a cross-linked modified loofah; (2) Adding a hydrophobic and lipophilic long-chain alkyl compound to the reaction solution after the cross-linking and grafting reaction in step (1), continuing the stirring reaction, and obtaining a luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material, wherein the mass ratio of the luffa pretreated with alkali solution to the long-chain alkyl compound is 1:(0.4-0.8).

2. The preparation method of the luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material according to claim 1, characterized in that: The step (1) specifically comprises adding the loofah pretreated with alkali solution into ethanol, adding bisphenol diglycerol ether, and adding an organic acid as a catalyst to carry out a cross-linking grafting reaction, wherein the mass ratio of the loofah pretreated with alkali solution, bisphenol diglycerol ether, and the organic acid is 1: (0.1-0.3): (0.03-0.07).

3. The preparation method of the luffa-based cross-linked hydrophobic lipophilic modified oil-absorbing material according to claim 2, characterized in that, The organic acid is one of formic acid and acetic acid.

4. The preparation method of the luffa-based cross-linked hydrophobic lipophilic modified oil-absorbing material according to claim 2, characterized in that, The cross-linking and grafting reaction in step (1) is carried out by stirring at 40-60° C. for 6-10 hours.

5. The method for preparing the luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material according to claim 1, wherein: The hydrophobic and lipophilic long-chain alkyl compound is a hydrophobic and lipophilic alkylene oxide.

6. The method for preparing the luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material according to claim 1, wherein: After adding the hydrophobic and lipophilic long-chain alkyl compound in step (2), stirring and reacting at 40-60° C. for 6-10 hours is continued. After the reaction, suction filtration, repeated washing with ethanol and drying are performed to obtain the luffa-based cross-linked hydrophobic and lipophilic modified material.

7. The method for preparing the luffa-based cross-linked hydrophobic and lipophilic modified oil-absorbing material according to claim 1, wherein: The alkaline solution pretreatment is to soak the loofah in a 2% to 15% NaOH aqueous solution, stir and treat it at 60 to 100° C. for 2 to 5 hours, and then wash it with deionized water until it is neutral.

8. A loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material, characterized in that: The invention is prepared by the preparation method of the loofah-based cross-linked hydrophobic and lipophilic modified oil-absorbing material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of hydrophobic oleophylic adsorbent by taking towel gourd cotton as raw material

    CN111569839A

  • Raspberry-like super-hydrophobic oleophylic cotton fiber oil-water adsorption / separation membrane as well as preparation method and application thereof

    CN111632581A

  • Preparation method and application of oleophylic hydrophobic high-activity microorganism-loaded composite cellulose / loofah sponge aerogel

    CN116875586A

  • Polyfunctional group modified loofah sponge heavy metal adsorbent and preparation method thereof

    CN118162115A